2015
DOI: 10.1002/ange.201501607
|View full text |Cite
|
Sign up to set email alerts
|

Direct Catalytic Asymmetric Aldol Reaction of an α‐Azido Amide

Abstract: A direct aldol reaction of an a-azido 7-azaindolinylamide, promoted by a Cu-based cooperative catalyst, is documented. Aromatic aldehydes bearing an ortho substituent exhibited diastereodivergency depending on the nature of the chiral ligands used. Smooth reactions with ynals highlighted the broad substrate scope. A vicinal azido alcohol unit in the product allowed direct access to the corresponding aziridine and facile hydrolysis of the 7-azaindolinylamide moiety furnished enantioenriched b-hydroxy-a-azido ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 60 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…The authors also found that aromatic aldehydes without an ortho substituent gave only the syn ‐aldol products, irrespective of the chiral ligands used. Moreover, 2‐flourobezaldehyde failed to yield any product under the catalysis of mesitylcopper/ 140 . These results hinted that the steric effects at the ortho position are crucial for obtaining anti products.…”
Section: Metal Complex‐catalyzed Diastereodivergent Reactionsmentioning
confidence: 96%
See 1 more Smart Citation
“…The authors also found that aromatic aldehydes without an ortho substituent gave only the syn ‐aldol products, irrespective of the chiral ligands used. Moreover, 2‐flourobezaldehyde failed to yield any product under the catalysis of mesitylcopper/ 140 . These results hinted that the steric effects at the ortho position are crucial for obtaining anti products.…”
Section: Metal Complex‐catalyzed Diastereodivergent Reactionsmentioning
confidence: 96%
“…Recently, Kumagai, Shibasaki, and co‐workers developed another diastereodivergent direct aldol reaction of α‐azido amide 176 and ortho ‐substituted aromatic aldehydes 175 for the synthesis of β‐hydroxy‐α‐azido amides 177 , employing co‐operative catalysis (Scheme ) . The use of different chiral ligands with mesitylcopper induced the diastereodivergence in the reaction.…”
Section: Metal Complex‐catalyzed Diastereodivergent Reactionsmentioning
confidence: 99%
“…In the latter case, metal-chiral phosphine catalyst systems have proven to be uniquely successful catalyst systems, as the diverse range of chiral bisphosphine, phosphoramidite, and P,N ligands available have enabled the development of a range of stereodivergent reactions. 38 39 40 41 42 43…”
Section: Mono-catalysismentioning
confidence: 99%
“…Recently,w ei dentified that the 7-azaindoline amides erved as al atent enolate in the carboxylic acid oxidation state in the contexto fs oft Lewis acid/hard Brønsted base cooperative catalysis. [12,13] Based on the rich chemistryo ft he azide functionality in organic synthesis, [14] we focused on the a-azidoa mide as al atent enolatet oi nstallt he azido group, whichc an be used as am asked amine and for azide-specific reactions. The use of a-azido carbonyl compounds for enolate chemistry has been scarcely explored in aldol reactions, [15] and to the best of our knowledge, no example of aM annich reaction is reported in the literature.…”
mentioning
confidence: 99%
“…As imilar trend was observed for Brsubstituted imines 3j and 3k but o-F substituted imine 3i gave the product 6i with high enantioselectivity,s uggesting that steric factors were responsible for the loss in enantioselectivity (entries8-11). Other imines, for example, p-CF 3 substituted imine 3l and heteroaromatic imines 3m and 3n,c ould be used in the present protocol to give the product with highs tereoselectivity (entries [12][13][14]. The thienyl group might competitively coordinate to the Cu I catalystt or etard the reaction and al ongerr eaction time was needed( entry 14).…”
mentioning
confidence: 99%